Pemaafan Pasca Perceraian pada Perempuan Korban Perselingkuhan di Yogyakarta - Fira Afiah; Andhita Dyorita Khoiryasdien (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Forgiveness is a change in the attitude of an individual who has been hurt so that he does not retaliate with the same action towards the person who has hurt him. This provides more peace in the heart. Forgiveness consists of three aspects which include Avoidance motivation, Revenge motivation and Beneviolence motivation. Female victims of infidelity tend to feel negative emotions for longer than male victims. Therefore, to eliminate negative emotions that cause psychosomatic symptoms in the victim, forgiveness is necessary. Through forgiveness, the heart of a woman who is a victim of infidelity no longer bears the psychological pain resulting from the injustice she experienced. This research is qualitative research that describes forgiveness among women victims of infidelity after divorce. The subjects of this research were women who were cheated on and divorced and their nieces The interview results from this research explained that the subjects had forgiven the perpetrator as evidenced by the absence of avoidance, desire for revenge and being able to empathize with the perpetrator. It was also found that forgiveness is influenced by several factors including emotional intelligence, the emergence of empathy, relationship quality, rumination, and personal factors. After forgiving the subject felt more at peace.